KPI Selection Using The AHP Method on SOE X - Berliana, Regine Rahmada; Sulistyo, Budi; Suwarsono, Litasari Widyastuti (IPTEK Journal of Proceedings Series, 2020)
PT X (Persero), a state-owned enterprise under the Ministry of Indonesia SOEs (KBUMN), is required to set up the Key Performance Indicators (KPI) Regulations based on the Assessment Criteria for Performance Excellence (KPKU). The re-weighting of KPIs using the Analytical Hierarchy Process (AHP) method is conducted by selecting performance indicators based on five perspectives. Based on the study results, selected performance measures for financial and market perspectives are cash position, cash-to-cash time cycle, income, and financial operations efficiency. Selected performance measures for customer focus perspective are customer complaints, complaint management, effective complaint resolution, and warranty claims; customer satisfaction and dissatisfaction; and retention, acquisition, and loss of customers and customer accounts. Selected performance measures for product and process effectiveness perspective are product performance, work system performance, improved performance of administrative functions and other supporting functions; and indicators of internal responsiveness. Selected performance measures for the perspective of workforce focus are turnover and effectiveness of training, retraining, or cross-functional training. Selected performance measures for leadership, governance, and community responsibility perspectives are the company's contribution to social welfare, achievements worthy of note in this field; and environmental, legal, and regulatory compliance.